2017
DOI: 10.1002/pon.4490
|View full text |Cite
|
Sign up to set email alerts
|

Does age matter? Comparing post‐treatment psychosocial outcomes in young adult and older adult cancer survivors with their cancer‐free peers

Abstract: AYA cancer survivors experience a significantly higher risk of psychosocial distress than both their cancer-free peers and OA survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 28 publications
2
69
0
Order By: Relevance
“…Other studies in AYA cancer survivors have reported higher psychological distress compared with cancer-free persons. [11][12][13] Reasons for similar levels of distress in Swiss AYA cancer survivors compared with controls might be the well-functioning health-care system in Switzerland providing survivors with needed support to function well psychologically and an in general good (re-) integration into work and social life after having been cured from cancer as indicated by another study in the same sample of Swiss AYA cancer survivors where we have found no significant differences for employment and marital status. 29 In our sample, survivors with migration background were more likely to report overall distress compared with survivors without migration background.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other studies in AYA cancer survivors have reported higher psychological distress compared with cancer-free persons. [11][12][13] Reasons for similar levels of distress in Swiss AYA cancer survivors compared with controls might be the well-functioning health-care system in Switzerland providing survivors with needed support to function well psychologically and an in general good (re-) integration into work and social life after having been cured from cancer as indicated by another study in the same sample of Swiss AYA cancer survivors where we have found no significant differences for employment and marital status. 29 In our sample, survivors with migration background were more likely to report overall distress compared with survivors without migration background.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies found that AYA cancer survivors reported poorer psychological health compared with cancer‐free persons and compared with persons diagnosed at a younger or older age . More than a quarter of AYA cancer patients and survivors reported psychological distress, and more than 80% of AYA cancer survivors had not spoken to a health‐care professional about their problems .…”
Section: Introductionmentioning
confidence: 99%
“…AYAs have emerged as a unique group in the clinical setting that requires specialized and cautious care and practice guidelines when facing the specific challenge of cancer diagnosis [17,18]. The previously limited amount of studies on AYAs has recently been increasing, examining not only their HRQoL and health behaviors, but also psychosocial outcomes [19,20]. HRQoL in AYAs has already been studied in Germany [21], the United Kingdom [22] and the United States [23].…”
Section: Introductionmentioning
confidence: 99%
“…As such, AYAs diagnosed with cancer during adolescence appear at an increased risk of problems related to their mental health. Indeed, studies have demonstrated that AYA survivors of cancer during adolescence report elevated levels of psychological distress in comparison to matched cancer-free controls (Seitz et al, 2010), those diagnosed during childhood (Kazak et al, 2010) and adulthood respectively (Lang et al, 2018). Further, research indicates that receiving a cancer diagnosis prior to age 25 leads to a higher risk of suicide (Gunnes et al, 2017) and being prescribed anxiolytics and hypnotics (Johannsdottir et al, 2018).…”
Section: Introductionmentioning
confidence: 99%